Iowa Birdline update, November 2, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for November 2, 1992. The highlights for the update include sightings of an abundance of Cedar Waxwings and lingering American Robins, and the season's first reports of a Common Redpoll and Snow Bunting. Also included are handwritten notes with sightings of huge flocks of Lapland Longspurs in addition to the diving Ducks and Loons that are moving into the state. Epson - sheet feed/flatbed